Conflict-free trajectory planning for urban air mobility based on an airspace-resource-centric approach - Dai, Wei (2022)
Urban air mobility (UAM) has been attracting stakeholders' attention for its great potential in playing an important role in future urban traffic systems. Expected high density of UAM operation requires advanced management strategy of airspace resources. In this paper, we present an Airspace-Resources-Centric (ARC) approach for UAM flight planning. In the first place, an ARC concept for urban airspace management is developed. Then a method for 4D trajectory planning with optimal airspace utilization was designed under the concept. The method consists three steps. Firstly, a flight level is assigned to each flight plan. Secondly, an optimal 3D path is generated by A* algorithm and is smoothed. Lastly, 4D trajectory generation is modeled as a mathematical optimization problem, and is solved by a commercial solver. Numerical simulation results show that the method plans trajectory for UAM with less than 1 second computational time per flight.